Refleksi Metafisis Perilaku Bom Bunuh Diri dan Tantangan Bagi Pendidikan Agama Islam - Fahmi, Muhammad; Achmad Muhibin Zuhri; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2022)
This article documents the metaphysical reflections in suicide bombing behavior and the challenges for Islamic Religious Education (PAI) in Indonesia. Through library research using content analysis as the analytical method, several findings are produced. It is found that the factors driving suicide bombing behavior in Indonesia include ideological, cultural, socio-economic, geographic, shallow religious understanding, disappointment towards authorities, injustice, and geographical factors. Ideological factors occupy a dominant position when supported by other factors. The metaphysical meaning in suicide bombing behavior can be approached through "metaphysics of relational and substantial substances". The relational substance includes "The One and the Many"; "The Permanent and the Changing"; "The Transcendent and the Immanent". Suicide bombing behavior is based on individual or group actions, all grounded in a belief directed towards The One. The mode of suicide bombing behavior can also change, but it remains destructive. The belief in carrying out God's command represents a transcendent spiritual value, while the bomb explosions planned by organized groups carry an immanent value. From the perspective of substantialistic metaphysics (autonomy and static), suicide bombing behavior places violence as the most fundamental and widespread layer (autonomous), independent and constant (static) reality. Radical ideologies, extremism, fundamentalism, exclusivism, militancy contribute to suicide bombing behavior. This poses a particular challenge for Islamic Religious Education (PAI). The construction of PAI materials must be tolerant, moderate, anti-radicalism, and counter-terrorism. PAI should be built based on the teachings of Islam as rahmatan lil ‘alamin (a mercy for all creations).